Relationship between Stock Market Volatility, Stock Market Liquidity and Financial Performance of Non-Financial Firms Listed on Pakistan Stock Exchange - Qasim, Saleem; Sophee Sulong, Bin Balia; Abu Hassan, Bin Md. Isa (Human Resource Management Academic Research Society, 2019)
This paper analyzed the empirical relationship between different measures of stock market volatility, traded volume, market and accounting measures of financial performance of 260 firms panel data listed on Pakistan Stock Exchange using Generalized Autoregressive Conditional heteroskedasticity (GARCH) and Generalized moments methods (GMM). The study found that financial performance has significant positive relation with traded volume and significant negative relationship with stock market volatility both in two measures. The study used both microeconomic and macroeconomic measures to calculate stock market volatility and both measures have significant effects on financial performance.